Modeling and simulation of a control system of wheels of wheelset - Andrzej Chudzikiewicz; Juraj Gerlici; Magdalena Sowińska; Anna Stelmach; Wojciech Wawrzyński (Archives of Transport, 2020)
Modern light rail vehicles, such as a tram or rail bus, due to the need to provide mobility for the elderly or disabled people and the requirements of operators operating passenger rail transport or transport in urban areas must have a 100% low floor. Structurally, this is associated with the use of wheelset with independently rotating wheels (IRW) in such vehicles. It is also possible to use a bogie structure without the use of a wheelset axle by mounting the wheels directly in the side parts of the bogie frame. This construction is more complex and will not be discussed in this article. Bearing in mind the dynamic behavior of such vehicles during operation (lateral stability, profile wear) in various driving conditions (curve traffic, crossovers) and taking into account operating costs, it becomes necessary to install wheel rotation control systems to maintain center movement mass of the wheelset around the centerline of the track. The subject of the article will be considerations on modeling and simulation of rail vehicle bogie motion with IRW sets including the wheel control system. Nominal and mathematical models of the analyzed vehicle will be presented, as well as a controlled strategy based on the comparison of the angular velocities of the wheels of the wheelset A review of works on solutions of such systems will be presented, and a control concept will be proposed. The summary contains conclusions regarding the possibility of practical use of the proposed method of steering wheels of a wheelset in the c ase of independently rotating wheels.